Effects of big-five personality traits on the quality of relationship and satisfaction in Chinese coach-athlete dyads - yANG, S.; JOWETT, S.; Chan, Derwin (2015)
© 2014 John Wiley & Sons A/S. The present study examined the influence of personality traits on the quality of the Chinese coach-athlete relationship and satisfaction through a dyadic research design. A total of 350 coach-athlete dyads completed a self-report instrument that assessed personality traits, as well as perceptions of relationship quality and satisfaction with training. Results revealed that: (a) actor effects (i.e., actor's personality will predict his or her own perceptions of relationship quality) of personality traits, namely, conscientiousness, extroversion, and neuroticism, on both coaches' and athletes' perceptions of relationship quality and (b) partner effects (an actor's own personality will predict his or her partner's perceptions of relationship quality) of only athletes' personality, namely, conscientiousness, extroversion, and neuroticism, on their coaches' perceptions of relationship quality. The findings suggested that each relationship member's personality trait contributed independently to relationship quality, and both actor and partner effects of the relationship quality on satisfaction with training were found to be significant. In Chinese sports culture, there presents a unique dynamics of personality and relationship quality among coach-athlete dyad.